Prenatal and Childhood Exposure to Phthalate Diesters and Thyroid Function in a 9-Year Follow-up Birth Cohort Study: Taiwan Maternal and Infant Cohort Study. (October 2017) - Huang, Han-Bin; Chuang, Chia-Jui; Su, Pen-Hua; Sun, Chien-Wen; Wang, Chien-Jen; Wu, Ming-Tsang; Wang, Shu-Li
Abstract : Background: Phthalates are widely used in industry, personal care products, and medications. Recent studies have suggested that phthalate exposure alters thyroid hormones. However, longitudinal studies concerning the association between phthalate exposure and thyroid function in children are scant. Therefore, we examined the association between pre- and postnatal phthalate exposure and thyroid function in children born in 2000–2001. Methods: We studied 181 mother–child pairs in central Taiwan and followed-up the children from 2000 to 2009 at 2, 5, and 8 years old. We measured serum levels of thyroxine (T4), free T4, triiodothyronine (T3), and thyroid-stimulating hormone in children by using radioimmunoassay. We quantified seven phthalate metabolites, representing the five most commonly used phthalates, in maternal and child urine samples by using liquid chromatography-tandem mass spectrometry. The metabolites were monoethylhexyl phthalate (MEHP), mono-(2-ethyl-5-hydroxyhexyl) phthalate (MEHHP), mono-(2-ethyl-5-oxohexyl) phthalate (MEOHP) derived from di(2-ethylhexyl) phthalate (DEHP), monomethyl phthalate (MMP), monoethyl phthalate (MEP), monobutyl phthalate (MBP), and monobenzyl phthalate (MBzP). We constructed a linear mixed model to examine these associations after adjustments for covariates. Results: The T4 levels were inversely associated with maternal urinary MEHHP ( β = −0.028 [95% confidence interval (CI) = −0.051, −0.006]) and MEOHP ( β = −0.027 [−0.050, −0.003]), with similar T3 levels being observed in boys, even when the children exposure levels were considered spontaneously. In the girls, the free T4 levels were inversely associated with levels of maternal urinary MEP ( β = −0.042), maternal urinary MBzP ( β = −0.050), and children's urinary MEHP ( β = −0.027). Conclusions: Early life phthalate exposure was associated with decreased thyroid hormone levels in young children. Abstract : Supplemental Digital Content is available in the text.